dsRNA as a novel tool to fight Verticillium diseases - from basics to future applications - Abdeldayem, Mohamed; Justus Liebig University Giessen (My University, 2025)
Verticillium infections affect a wide range of plant hosts and cause considerable losses for economically relevant crops like cotton, tomatoes, oilseed rape, and many others. The lifestyle of this soil-borne fungal pathogen further complicates the management strategies and is currently limited to cultural practices such as crop rotation and the use of resistant cultivars, aimed to reduce the presence of disease causing microsclerotia resting in the soil. V. longisporum is the latest characterized species with a nearly diploid genome and a narrower host range – in comparison to the better studied species, namely V. dahliae and V. albo-atrum – is a major threat to oilseed rape production in Europe and Canada. The lack of reliable management strategies led to the interest in exploring RNA interference (RNAi) based alternatives, using double-stranded (ds)RNA to target virulence genes identified from the closely related species V. dahliae. The dissertation covers the confirmation of RNAi machinery activity and targeted gene silencing using 450-500 bp (ds)RNA, followed by a hydroponic based infection assay development and in-vitro growth assay in 96-well-plates for scalability. Both assays were used to assess the plant protection potential for the selected gene targets, formulation development for stabilizing (ds)RNA, and (ds)RNA detection assay after spray application. The selected gene targets demonstrated variable effects on growth and virulence, resulting in different in-vitro growth patterns and disease severity after (ds)RNA addition. The results highlighted the necessity of gene target selection framework and revealed the challenges facing this approach to achieve a prolonged plant protection on a larger scale.
Keywords: RNA intereference; Verticillium; Spray induced gene silencing (SIGS); dsRNA; Plant protection; ddc:570